2016
DOI: 10.1136/openhrt-2015-000335
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of structured, hospital-based, nurse-led atrial fibrillation clinics: a comparison between a real-world population and a clinical trial population

Abstract: ObjectiveA previous randomised trial showed that structured, nurse-led atrial fibrillation (AF) care is superior to conventional AF care, although further research is needed to determine the outcomes of such care in a real-world setting. We compared the outcomes of patients in real-world, nurse-led, structured hospital AF clinics with the outcomes of a randomised trial of the efficacy of a nurse-led AF clinic, with respect to a composite outcome of cardiovascular-related hospitalisation and death.MethodsAll pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 29 publications
2
19
0
Order By: Relevance
“…The positive influence of the outpatient AF clinic, as presented in this study is comparable with prior research regarding outpatient AF clinics assessed in a clinical trial (academic) setting and in a real‐world setting . Although, these prior studies reported more hospitalizations (48 and 50), more major bleedings (6 and 5), higher mortality rates, and a higher number of serious adverse effects of medication, the difference in measurement periods should be taken into account. While the AF‐NET study presented 6 months follow‐up data, the results in the study of Hendriks et.al (2012) were indicated after 22 months and in the study of Qvist et.al (2016) after 14 months of follow‐up.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…The positive influence of the outpatient AF clinic, as presented in this study is comparable with prior research regarding outpatient AF clinics assessed in a clinical trial (academic) setting and in a real‐world setting . Although, these prior studies reported more hospitalizations (48 and 50), more major bleedings (6 and 5), higher mortality rates, and a higher number of serious adverse effects of medication, the difference in measurement periods should be taken into account. While the AF‐NET study presented 6 months follow‐up data, the results in the study of Hendriks et.al (2012) were indicated after 22 months and in the study of Qvist et.al (2016) after 14 months of follow‐up.…”
Section: Discussionsupporting
confidence: 82%
“…Therefore, no conclusion can be drawn regarding significant improvements over longer time periods. Despite significant differences in follow‐up periods, the procedure and positive influence of the outpatient AF clinic on AF‐patients outcomes as demonstrated in this study are comparable with previous studies . Nevertheless, future research should put effort in analyzing the patient relevant outcomes at 12 and 24 months, or comparing follow‐up data with similar retrospective data.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…[11][12][13] Studies suggest that specialized post-discharge follow-up by trained nurses represents an opportunity to improve the care and outcomes of patients with cardiovascular diseases. [14][15][16] Nurses may have more availability than physicians to conduct close follow-up, and may communicate with patients more effectively, particularly in terms of health education.…”
Section: Text Introductionmentioning
confidence: 99%